LEXICAL AND SYNTAX FEATURES OF ENGLISH AND ARABIC LEGAL DISCOURSE: A COMPARATIVE STUDY - EL-FARAHATY, Hanem (Comparative Legilinguistics, 2010)
This paper discusses the common lexical and grammatical features of legal discourse in English and Arabic.6 The rationale behind this analysis is to compare and contrast the discourse of both languages, list the similarities and differences between them and come up with the most problematic areas in legal translation. It is worth mentioning that features of Arabic legal discourse have not been researched before, thus, I have taken the features of legal English as headlights according to which I will analyze the corpus of Arabic legal documents. These features, however, are not specific to one particular type of written language of the law. By type of language is meant the different types of legal texts such as legislations, contracts, official documents, court proceedings, etc. For this purpose, authentic samples of different English and Arabic legal documents have been consulted. These texts, obtained from law professionals, include private legal documents such as tenancy agreements, employment contracts, correspondences between solicitors and clients, reports to the court, birth certificates, and marriage certificates. Other documents include selected legislative and international documents. To this effect, the United Nations (UN) website, other translation books such as Mansoor (1965), Hatim, Shunnaq and Buckley (1995) are consulted.